Original Yellowknife School House ... - Campbell, Sandy (University of Alberta Library, 2015)
Plaque on the outer wall reads \"Yellowknife's original school. Built in 1939. Mis Mildred Hall opened this school with a class of 32 students in September, 1939. The log school was moved from the Old Tow to this site in February 1987 by Yellowknife Education District No. 1 and the Yellowknife Heritage Committee.\" The log school house is located near Mildred Hall School. ...